Trauma in medieval society - Turner, Wendy J. (Wendy Jo), 1961-; Lee, Christina (Explorations in medieval culture, 2018)
This is an edited collection of articles from a variety of scholars on the history of trauma and the traumatized in medieval Europe. Looking at trauma as a theoretical concept, as part of the literary and historical lives of medieval individuals and communities, this volume brings together scholars from the fields of archaeology, anthropology, history, literature, religion, and languages. The collection offers insights into the physical impairments from and psychological responses to injury, shock, war, or other violence - either corporeal or mental. From biographical to socio-cultural analyses, these articles examine skeletal and archival evidence as well as literary substantiation of trauma as lived experience in the Middle Ages.